1988
DOI: 10.1046/j.1468-2982.1988.0804229.x
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Headache: The Possible Significance of Midline Structures

Abstract: The pathogenesis of cluster headache is unknown (see, for example, Ref. 1). With regard to the main component of cluster headache, the pain itself, little information exists both as to the origin and as to the nature of the pain. Existing theories concerning cluster headache pathogenesis have been rather unproductive. In the following, evidence from seemingly totally unrelated fields that, nevertheless, possibly has a bearing on cluster headache pathogenesis will be reviewed. On the tendency to bilaterality in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 33 publications
1
16
0
3
Order By: Relevance
“…[17][18][19][20][21][22][23] Thus, Hannerz and co-workers have found, in some patients, ipsilateral phlebographic changes in the superior ophthalmic vein and the cavernous sinus during attacks, suggestive of a venous vasculitis.19 Furthermore, blood flow changes indicating dilatation of the middle cerebral artery have been reposed on the painful side, both during and after attacks. 20 Hardebo has suggested that an inflammation in the cavernous sinus, possibly secondary to an upper airway infection, might damage the sympathetic fibers traversing the cavernous region.…”
Section: Commentsmentioning
confidence: 99%
“…[17][18][19][20][21][22][23] Thus, Hannerz and co-workers have found, in some patients, ipsilateral phlebographic changes in the superior ophthalmic vein and the cavernous sinus during attacks, suggestive of a venous vasculitis.19 Furthermore, blood flow changes indicating dilatation of the middle cerebral artery have been reposed on the painful side, both during and after attacks. 20 Hardebo has suggested that an inflammation in the cavernous sinus, possibly secondary to an upper airway infection, might damage the sympathetic fibers traversing the cavernous region.…”
Section: Commentsmentioning
confidence: 99%
“…No mechanism was suggested to link the two diseases and the authors concluded the absence of a causal relationship. Nevertheless, calcification located close to the midline structure is suggestive of hypothalamic impairment potentially implicated in CH as previously discussed [4,12].…”
Section: Clh and Other Lesion Sitesmentioning
confidence: 53%
“…The pathophysiology of P neurons remains unknown. Among the theories, a reduction in descending inhibitory control of the spinal trigeminal nucleus under the influence of hypothalamic-limbic structures is hypothesized [12]. This theory explains the pain, the autonomic signs and also the chronobiological aspects of the disease.…”
Section: Cluster Headachementioning
confidence: 99%
“…Muitos autores, como Sjaastad 14 , têm demonstrado, que os sintomas autonômicos podem aparecer também no lado contralateral à cefaléia, comprovando o envolvimento de estruturas centro -medianas cerebrais na fisiopatologia da CS. A CS no Ambulatório de Cefaléia da Santa Casa de São Paulo apresenta prevalência de 2,53% em relação às outras cefaléias, enquanto a literatura mostra uma variação de 0,09% a 0,4% 9,10 .É possível que esta diferença estatística deva-se ao fato de nosso ambulatório estar reservado para casos de cefaléia de difícil controle, ocorrendo triagem prévia.…”
Section: Discussionunclassified